Prepregs, laminates and molded products
By using prepregs containing reinforcing fibers, epoxy resins and thermoplastic resins, combined with welding technology, the problem of insufficient molding and bonding strength of complex shape components is solved, and the effects of rapid molding and high-strength bonding are achieved.
Patent Information
- Application Number
- CN202080036511.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-05-23
- Filing Date
- 2020-05-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-05-15
AI Technical Summary
In the prior art, when using a fiber-reinforced composite material formed by thermosetting resin and reinforced fibers, it is difficult to achieve rapid molding and high-strength jointing of complex-shaped components, and the traditional bonding method has problems of lowering material strength and insufficient bonding strength.
A prepreg containing reinforcing fibers, epoxy resins and thermoplastic resins is used to bond with the same or different components through welding technology to form a laminate with excellent tensile shear, out-of-plane tensile and impact bonding strength.
The rapid molding and high-strength joint of complex-shaped components is achieved, reducing the manufacturing process time and cost, while improving the overall performance of the material.
Smart Images

Figure CN113825788B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a prepreg comprising reinforcing fibers, an epoxy resin and a thermoplastic resin, a laminate comprising reinforcing fibers, a thermoplastic resin and a cured epoxy resin, and a molded product. Background Art
[0002] For the fiber-reinforced composite material formed by using thermosetting resin or thermoplastic resin as a matrix and combining it with reinforcing fibers such as carbon fiber and glass fiber, it is lightweight and has excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance, so it is used in many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and sports goods. However, these fiber-reinforced composite materials are not suitable for manufacturing parts and structures with complex shapes with a single molding process. In the above-mentioned uses, it is necessary to prepare parts formed by fiber-reinforced composite materials and then integrate them with the same or different parts. As a method for integrating fiber-reinforced composite materials formed by reinforcing fibers and thermosetting resins with the same or different parts, mechanical joining methods such as bolts, rivets, screws, and joining methods using adhesives can be used. In the mechanical joining method, since it is necessary to pre-process the process of the joining part such as the opening, the manufacturing process time becomes longer and the manufacturing cost increases. In addition, there is a problem of reduced material strength due to the opening. The bonding method using an adhesive requires a bonding step including preparation of the adhesive, application of the adhesive, and a curing step, which results in a long manufacturing process time and a problem that reliability cannot be fully satisfied in terms of bonding strength.
[0003] For fiber-reinforced composite materials using thermoplastic resins for the matrix, in addition to the above-mentioned mechanical joining methods and joining methods using adhesives, methods of joining components by welding can be applied, so there is a possibility that the time required for joining components can be shortened. On the other hand, regarding the joining strength required as a structural material, there are joining strengths in the tensile shear (in-plane shear) or out-of-plane tensile modes, and joining strengths against impact, and there is a problem that sufficient reliability cannot be obtained for all of the above-mentioned joining strengths.
[0004] Here, Patent Document 1 discloses a method of joining a fiber-reinforced composite material composed of a thermosetting resin and reinforcing fibers with an adhesive.
[0005] Patent Document 2 shows a method for integrating a component formed of a thermoplastic resin and a component formed of a fiber-reinforced composite material containing a thermosetting resin. That is, a thermoplastic resin film is laminated on the surface of a prepreg sheet formed of reinforcing fibers and a thermosetting resin and heated and pressurized to obtain a fiber-reinforced composite material. Thereafter, the obtained fiber-reinforced composite material is placed in a mold, and a thermoplastic resin is injection molded, and the formed thermoplastic resin component and the fiber-reinforced composite material are joined by injection molding.
[0006] Patent Document 3 describes a method for producing a laminate having a thermoplastic resin adhesive layer formed on the surface of a composite material composed of a thermosetting resin and reinforcing fibers, and describes that the laminate exhibits an adhesive effect with other members via the thermoplastic resin.
[0007] Patent Document 4 discloses a prepreg and a fiber-reinforced composite material thereof, wherein particles, fibers, or films containing a thermoplastic resin are arranged on the surface layer of a prepreg composed of reinforcing fibers and a thermosetting resin.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2018-161801
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 10-138354
[0012] Patent Document 3: Japanese Patent No. 3906319
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 8-259713 Summary of the invention
[0014] Problems to be solved by the invention
[0015] However, since the method disclosed in Patent Document 1 is a method of bonding fiber-reinforced composite materials formed of reinforcing fibers and thermosetting resins to each other using an adhesive, and the thermosetting resin is a matrix resin, welding cannot be applied as a bonding method between fiber-reinforced composite materials as it is. Since the curing of the adhesive takes time, there is a problem that time is required in the bonding process, and the bonding strength exhibited is insufficient.
[0016] In the method described in Patent Document 2, the bonding strength at the bonding portion between the thermosetting resin and the thermoplastic resin film in the fiber-reinforced composite material is insufficient.
[0017] The fiber-reinforced composite material disclosed in Patent Document 3 can be integrated by welding via a thermoplastic resin and exhibits excellent static bonding strength, but is insufficient in bonding strength against impact.
[0018] Patent Document 4 discloses that the interlaminar fracture toughness value can be improved by using particles, fibers or films containing a thermoplastic resin. However, in this method, the bonding strength at the boundary between the thermosetting resin and the thermoplastic resin in the fiber-reinforced composite material is insufficient.
[0019] Therefore, the object of the present invention is to provide a prepreg, a laminate and an integrated molded product, wherein the prepreg can be joined to the same or different parts by welding, and exhibits excellent tensile shear bonding strength, out-of-plane tensile bonding strength, and impact bonding strength, and can provide a laminate suitable as a structural material.
[0020] Means for solving problems
[0021] In order to solve the above-mentioned problems, the prepreg of the present invention has the following structure. That is, the prepreg includes the following components [A], [B] and [C]:
[0022] [A] Reinforcement fibers;
[0023] [B] Epoxy resin;
[0024] [C] Thermoplastic resin,
[0025] The average epoxy value of all epoxy resins contained in [B] is 2.0 meq. / g or more and 5.0 meq. / g or less, [C] is present on the surface of the prepreg, and in the prepreg, there are reinforcing fibers [A] contained in the resin regions including [B] and [C] astride the boundary surface between the two resin regions.
[0026] Furthermore, the laminate of the present invention has the following structure. That is, it contains a layer comprising the following constituent elements [A], [C] and [D]:
[0027] [A] Reinforcement fibers;
[0028] [C] Thermoplastic resin;
[0029] [D] Epoxy resin cured product,
[0030] The average epoxy value of all epoxy resins contained in [D] is 2.0 meq. / g or more and 5.0 meq. / g or less, and in the laminate, there is a reinforcing fiber laminate [A] contained in both resin regions across the boundary surface between the resin region containing [C] and the resin region containing [D].
[0031] Effects of the Invention
[0032] Prepreg of the present invention uses epoxy resin and thermoplastic resin, and these two are firmly joined, and can be well welded with parts of the same or different species, therefore, relative to the fiber reinforced composite material formed by thermosetting resin and reinforcing fiber in the past, the time required in the joining process can be shortened, and the molding of structural parts can be made high-speed. In addition, excellent tensile shear bonding strength, out-of-plane tensile bonding strength and impact bonding strength are shown, and a laminate excellent as a structural material can be obtained. For laminate of the present invention, by being applicable to computer uses such as aircraft structural parts, blades of windmills, automotive structural parts and IC trays, shells of notebook computers, etc., not only can excellent performance as a structure be shown, and if prepreg of the present invention is used, the molding time and molding cost of the products involved in the above-mentioned uses can also be greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The schematic diagram of the prepreg or laminated body according to the present invention is shown in FIG. Figure 2 A view of a cross section of the plane of the prepreg or the plane of the laminate involved.
[0034] Figure 2 It is a schematic diagram of a cross section perpendicular to the plane of the prepreg or the plane of the laminate in the present invention, and is a diagram useful for explaining the method of measuring the roughness average length RSm and the roughness average height Rc. DETAILED DESCRIPTION
[0035] As the component [A] reinforcing fiber used in the present invention, there are glass fiber, carbon fiber, metal fiber, aromatic polyamide fiber, polyaramid fiber (polyaramid), aluminum oxide fiber, silicon carbide fiber, boron fiber, basalt fiber, etc. The above substances can be used alone or in combination of two or more. For the above reinforcing fibers, surface treatment can be applied. As surface treatment, there are metal deposition treatment, treatment using a coupling agent, treatment using a sizing agent, and adhesion treatment of additives. The above reinforcing fibers also include reinforcing fibers with conductivity. As reinforcing fibers, it is preferred to use carbon fibers with a small specific gravity, high strength, and high elastic modulus.
[0036] Commercially available products of carbon fibers include "Torayca (registered trademark)" T800G-24K, "Torayca (registered trademark)" T800S-24K, "Torayca (registered trademark)" T700G-24K, "Torayca (registered trademark)" T700S-24K, "Torayca (registered trademark)" T300-3K, and "Torayca (registered trademark)" T1100G-24K (all manufactured by Toray Co., Ltd.).
[0037] The form and arrangement of the reinforcing fibers can be appropriately selected from: a form in which the reinforcing fibers are arranged in one direction; a laminate of objects arranged in one direction; or a woven form, etc. In order to obtain a lightweight laminate with a higher level of durability, in each prepreg, the reinforcing fibers are preferably in the form of long fibers (fiber bundles) or continuous fibers such as woven fabrics in which the reinforcing fibers are arranged in one direction.
[0038] The reinforcing fiber bundle may be composed of multiple fibers of the same form, or may be composed of multiple fibers of different forms. The number of reinforcing fibers constituting one reinforcing fiber bundle is usually 300 to 60,000, and if the manufacture of the substrate is considered, it is preferably 300 to 48,000, and more preferably 1,000 to 24,000. It may also be a range formed by a combination of any of the upper limits and any of the lower limits.
[0039] For the reinforcing fiber of component [A], if the strand tensile strength measured according to the resin impregnation strand test method of JIS R7608 (2007) is 5.5 GPa or more, a laminate having excellent bonding strength in addition to tensile strength can be obtained, which is preferred. If the strand tensile strength is 5.8 GPa, it is further preferred. The bonding strength mentioned here refers to the tensile shear bonding strength determined according to ISO4587:1995 (JIS K6850 (1994)) and the out-of-plane tensile bonding strength determined according to ASTM D7291-07.
[0040] The component [B] used in the present invention is an epoxy resin, and the average epoxy value of all epoxy resins contained therein is 2.0 meq. / g or more and 5.0 meq. / g or less. Here, as an example, the average epoxy value of all epoxy resins contained is calculated as follows when two components, epoxy resin 1 and epoxy resin 2, are included.
[0041] Average epoxy value (meq. / g) = (mass fraction of epoxy resin 1 / epoxy equivalent of epoxy resin 1 + mass fraction of epoxy resin 2 / epoxy equivalent of epoxy resin 2) / (mass fraction of epoxy resin 1 + mass fraction of epoxy resin 2) × 1000
[0042] Here, epoxy equivalent refers to the value obtained according to the method described in JIS K7236 (2009). By making the average epoxy value of all epoxy resins contained 2.0 meq. / g or more and 5.0 meq. / g or less, as a laminate or a molded product, excellent tensile shear bonding strength, out-of-plane tensile bonding strength and impact bonding strength are shown. In addition, it is more preferred that the average epoxy value of all epoxy resins contained is 2.5 meq. / g or more and 4.0 meq. / g or less. It can also be a range formed by combining any of the above upper limits and any of the lower limits.
[0043] The composition containing component [B] contained in the prepreg of the present invention preferably has a bending fracture strain of 8% or more in a state where the degree of cure is 90% or more. This is preferred because when the laminate of the present invention contains the above-mentioned cured product, the impact bonding strength when the laminate is bonded to a component is excellent. That is, in the laminate of the present invention, it is preferred that the bending fracture strain of component [D], the epoxy resin cured product, is 8% or more.
[0044] The bending fracture strain can be obtained by a three-point bending test based on JIS K7171 (1994). When the bending fracture strain of the component [B] contained in the prepreg is obtained when the degree of cure is 90% or more or the bending fracture strain of the component [D] contained in the laminate, on the basis of determining the type of epoxy resin, a composition is prepared for the same uncured resin in the same manner as the degree of cure measurement described later, and cured for the measurement of the bending fracture strain. In addition, there is no particular upper limit for the bending fracture strain, and the conventional epoxy resin cured product has an upper limit of 100%.
[0045] In order to make component [B] a state where the degree of cure is 90% or more, this can be achieved by heat curing the component [B] epoxy resin and the epoxy resin composition before curing, which is determined as a curing agent, under predetermined conditions. The so-called heat curing under predetermined conditions means first heating at 135°C for 2 hours or 180°C for 2 hours, and then further heating as needed until the degree of cure reaches 90% or more. The degree of cure of the epoxy resin cured product obtained by heating at 135°C for 2 hours or 180°C for 2 hours is measured, and if the degree of cure is 90% or more, the epoxy resin cured product can be used for property evaluation. If the degree of cure is less than 90% under the conditions of heating temperature and time at 135°C for 2 hours or 180°C for 2 hours, post-heating at 180°C for 2 hours is applied and the degree of cure is confirmed. If the degree of cure is less than 90% under the state of post-heating, heating at 200°C for 1 hour, 220°C for 1 hour, and 240°C for 1 hour is added in sequence until the degree of cure reaches 90% or more. When the degree of cure does not reach 90% even after heating at 240°C for 1 hour, heating at a temperature of 300°C or lower is performed until the degree of cure reaches 90% or more, thereby obtaining a target epoxy resin cured product for property evaluation.
[0046] Here, the degree of cure is the following value, that is, for the respective exothermic values of the epoxy resin of the constituent element [B] and the epoxy resin composition before curing determined as the curing agent, and the cured product of the above epoxy resin, when differential scanning calorimetry is performed at a heating rate of 10°C / min in an inert gas atmosphere, the area of each peak that appears as an exothermic reaction is calculated separately, and the value is obtained by the following formula. It is also possible to prepare a resin having the same structure as the substance determined as the epoxy resin and the curing agent separately from the constituent element [B] contained in the prepreg for measurement. Here, when the curing agent cannot be determined, 4,4'-diaminodiphenyl sulfone can be used as the curing agent in the above composition. In addition, it is preferred to use a curing catalyst, a viscosity modifier, etc., which are described later in the examples, as elements that can constitute the above composition, and there is no particular limitation as long as it does not affect the measurement results.
[0047] Curing degree (%) = ((heat release of the composition containing epoxy resin before curing) - (heat release of the cured product of epoxy resin)) / (heat release of the composition containing epoxy resin before curing) × 100
[0048] For the component [D] epoxy resin cured product in the present invention, it can be obtained by heating and curing the component [B] epoxy resin. For the determination of the curing of the component [D] contained in the laminate, if the area (residual exotherm) of the peak that appears as an exothermic reaction when the laminate is subjected to differential scanning calorimetry at a heating rate of 10°C / min in an inert gas atmosphere is 50J / g or less, it can be determined to be substantially a cured product. Alternatively, when the epoxy resin composition before curing can be determined, the degree of curing is calculated by the above formula, and if it is 90% or more, it can be regarded as a cured product. When the prepreg of the present invention is used, the epoxy resin corresponds to the component [B]. The laminate of the present invention does not necessarily have to be made via a prepreg, and can also be made by the resin transfer molding method described later.
[0049] Examples of the epoxy resin used in component [B] include bisphenol-type epoxy resins such as bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, bisphenol AD-type epoxy resins, and bisphenol S-type epoxy resins, brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether, epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, phenol Novolac-type epoxy resins, cresol Novolac-type epoxy resins, and other Novolac-type epoxy resins, N,N,O-triglycidyl-m-aminophenol, N,N, Glycidylamine type epoxy resins such as O-triglycidyl p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-phenylenediamine, N,N-diglycidyl aniline, N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, triglycidyl isocyanurate, etc.
[0050] The component [B] of the present invention contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 400 to 3000 based on 100 parts by mass of the total epoxy resin contained, so that a laminate and a molded product having excellent impact bonding strength can be obtained, which is a preferred embodiment. A more preferred embodiment is to contain 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 1000 to 3000 based on 100 parts by mass of the total epoxy resin contained.
[0051] Examples of curing agents for epoxy resins include dicyandiamide, aromatic amine compounds, phenol Novolac resins, cresol Novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea addition amines, formic hydrazide, formamide, and polythiol. Among them, dicyandiamide or aromatic amine compounds are preferred because they provide good reactivity and excellent mechanical properties and heat resistance as a cured product. Examples of the aromatic amine compound include 3,3'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-4,4'-diaminodiphenyl sulfone, 3,3'-diethyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-dimethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenyl sulfone, 3,3'-diisopropyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-diethyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenyl sulfone, 3,3'-di-tert-butyl-5,5'-diisopropyl-4,4'-diaminodiphenyl sulfone, 3,3',5,5'-tetra-tert-butyl-4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, etc.
[0052] In addition, for the component [B] epoxy resin, it is preferred that a thermoplastic resin component soluble in the epoxy resin is contained in a dissolved state as a viscosity modifier. The above-mentioned thermoplastic resin component is another thermoplastic resin component different from the component [C]. Here, "soluble in epoxy resin" means that there is a temperature range in which a uniform phase is formed by heating or heating and stirring the resin obtained by mixing the thermoplastic resin component with the epoxy resin. Here, "forming a uniform phase" means that a state in which no separation can be obtained under visual observation. Here, "dissolved state" means that the epoxy resin containing the thermoplastic resin component is placed in a certain temperature range and becomes a uniform phase. If it becomes a uniform phase in a certain temperature range, it does not matter even if separation occurs outside the temperature range, for example at room temperature.
[0053] As a thermoplastic resin component soluble in the epoxy resin of the constituent element [B], in general, a thermoplastic resin having a bond selected from the group consisting of a carbon-carbon bond, an amide bond, an imide bond, an ester bond, an ether bond, a carbonate bond, a carbamate bond, a thioether bond, a sulfone bond and a carbonyl bond in the main chain is preferred. In addition, for the thermoplastic resin component, it is also possible to partially have a cross-linked structure, and it may be crystalline or amorphous. In particular, it is suitable to be selected from the group consisting of polyamide, polycarbonate, polyoxymethylene, polyphenylene ether, polyphenylene sulfide, polyarylate, polyester, polyamide-imide, polyimide, polyetherimide, polyimide of phenyltrimethylindane structure, polysulfone, polyethersulfone, polyetherketone, polyetheretherketone, polyarylamide, polyvinyl formal, polyvinyl butyral, phenoxy resin, polyether nitrile and polybenzimidazole.
[0054] The thermoplastic resin constituting component [C] is not particularly limited, and examples thereof include polyester resins (polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, liquid crystal polyester, etc.), polyolefin resins (polyethylene, polypropylene, polybutene, etc.), styrene resins, urethane resins, and polyoxymethylene, polyamide resins (aliphatic polyamides such as polyamide 6 and polyamide 66, semi-aromatic polyamides, alicyclic polyamides, etc.), polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyketone, polyarylene ether ketone (polyether ketone, polyether ether ketone, polyether ketone ketone, etc.), polyarylate, polyether nitrile, phenol resin, phenoxy resin, etc. Furthermore, these thermoplastic resins may be copolymers, modified products, and / or resins obtained by mixing two or more kinds of the above-mentioned resins.
[0055] In order to improve the impact resistance, an elastomer or a rubber component can be added to the epoxy resin or the thermoplastic resin. In addition, according to the use, the epoxy resin or the thermoplastic resin may also contain other fillers and additives as appropriate, without prejudice to the purpose of the present invention. For example, inorganic fillers, flame retardants, conductivity imparting agents, nucleating agents, ultraviolet absorbers, antioxidants, vibration damping agents, antibacterial agents, insect repellents, deodorants, anti-coloring agents, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, defoamers, coupling agents, etc. can be cited.
[0056] In the prepreg of the present invention, there are reinforcing fibers [A] that are included in both resin regions, straddling the boundary surface between the resin region containing [B] and the resin region containing [C].
[0057] The presence of [A] included in both resin regions and extending across the boundary surface between the two resin regions can be confirmed by observing a cross section cut perpendicularly to the plane direction. Figure 2 To illustrate an example. Figure 2 In the observed image 9, in the case of the prepreg, the resin region 7 containing the component [C] is in close contact with the resin region 8 containing the component [B], and the surface formed by the resin region 7 containing the component [C] and the resin region 8 containing the component [B] is shown as the boundary surface 10. In addition, there are a plurality of components [A] 6 on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 containing the component [C] and the resin region 8 containing the component [B]. In the state where the components [C] and [B] are in contact around the reinforcing fibers, it can be said that the reinforcing fibers are in a state of "being included in these two resin regions across the boundary surface".
[0058] Furthermore, when the prepreg of the present invention is viewed from above, in a cross section perpendicular to the plane of the prepreg including the fibers of [A] existing across the above-mentioned two resin regions, obtained from a direction that differs by 45 degrees (whether clockwise or counterclockwise) with respect to the fiber direction of any [A] contained in the above-mentioned two resin regions, that is, in a cross section obtained by cutting perpendicularly with respect to the plane direction of the prepreg, it is preferred that the cross-sectional curve formed by the boundary surfaces of the two resins has a roughness average length RSm of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
[0059] In addition, it is preferred that the resin region containing [B] and the resin region containing [C] are each formed in a layered manner and adjacent to each other, thereby forming the aforementioned boundary surface. For example, the resin region containing [B] and the resin region containing [C] are formed in a layered manner and adjacent to each other, Figure 2 The state in which two continuous resin regions exist adjacent to each other as shown can be confirmed by observing a cross section cut perpendicularly to the plane direction of the prepreg.
[0060] The presence of the reinforcing fibers [A] contained in the resin region containing the component [B] and the resin region containing the component [C] across the boundary surface between the two resin regions improves the strength of the resin region containing the component [C] and improves the bonding strength. The component [A] present on the boundary surface chemically and / or physically combines with the components [B] and [C], thereby improving the adhesion with the resin region containing the component [B] and the resin region containing the component [C]. The number of components [A] present on the boundary surface may be one or more, and the upper limit is not particularly limited, but is 200 within the observation range described below.
[0061] The boundary surface between the resin region containing the component [B] and the resin region containing the component [C] can be observed as follows, that is, in the prepreg viewed from above, that is, from a viewpoint perpendicular to the plane direction of the prepreg, from a direction that is 45 degrees (whether clockwise or counterclockwise) different from any fiber direction of [A] contained in the above two resin regions, in a cross section perpendicular to the plane of the prepreg containing the fibers of [A] existing across the above two resin regions. In the cross section, by observing the resin region in the boundary surface, the adhesion in the fiber direction and the direction perpendicular to it can be evaluated simultaneously.
[0062] In the above cross-sectional observation, if the roughness average length RSm of the cross-sectional curve formed by the boundary surface defined by JIS B0601 (2001) is less than 100 μm, not only chemical and / or physical bonding force, but also mechanical bonding force such as interweaving is added, and the resin area containing component [B] and the resin area containing component [C] become difficult to peel off, so it is preferred. The lower limit value is not particularly limited, but from the perspective of avoiding the reduction of mechanical bonding force caused by stress concentration, it is preferably 15 μm or more. In addition, by making the roughness average height Rc of the cross-sectional curve greater than 3.5 μm, not only the mechanical bonding force caused by interweaving can be manifested, but also the component [A] existing on the boundary surface is chemically or / and physically combined with the component [B] and the component [C], and the adhesion with the resin area containing component [B] and the resin area containing component [C] is improved, so it is preferred. The more preferred range of the roughness average height Rc of the cross-sectional curve is 10 μm or more (component [A] becomes easy to be included in the two resin regions and the adhesion is further improved), and particularly preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 100 μm or less from the viewpoint of avoiding a decrease in mechanical bonding strength caused by stress concentration.
[0063] Here, as a method for measuring the roughness average height Rc and the roughness average length RSm of the cross-sectional curve, a known method can be used. For example, after the component [B] is solidified, a method for measuring by a cross-sectional image obtained using X-ray CT, a method for measuring by an elemental analysis distribution image using an energy dispersive X-ray spectrometer (EDS), or a method for measuring by a cross-sectional observation image using an optical microscope or a scanning electron microscope (SEM) or a transmission electron microscope (TEM). During the observation, in order to adjust the contrast, the component [B] and / or the component [C] may also be stained. In the image obtained by any of the above methods, the roughness average height Rc and the roughness average length RSm of the cross-sectional curve are measured within a range of 500 μm square.
[0064] An example of a method for measuring the roughness average height Rc and the roughness average length RSm of a cross-sectional curve (Method 1 for measuring cross-sectional curve elements) is used. Figure 2 . The end 11 of the rectangular observation image 9 on the side of the resin region containing the component [B] is used as a reference line, and a base line perpendicular line 12 is drawn at intervals of 5 μm from the resin region 8 containing the component [B] toward the resin region 7 containing the component [C]. The point where the base line perpendicular line drawn from the reference line first intersects the component [C] is plotted, and the line connected by the plotted points is set as a cross-sectional curve 13. The obtained cross-sectional curve 13 is screened based on JIS B0601 (2001), and the roughness average height Rc and the roughness average length RSm of the cross-sectional curve 13 are calculated.
[0065] Furthermore, from the viewpoint of exhibiting excellent mechanical properties, it is preferred that the resin region containing [B] and the resin region containing [C] are each formed in a layered state and are adjacent to each other to form the boundary surface.
[0066] The thermoplastic resin component [C] in the prepreg of the present invention preferably has a weight per unit area of 10 g / m 2 If 10g / m 2 More preferably, it is 20 g / m 2 The upper limit is not particularly limited, but is preferably 500 g / m 2 This is because the amount of thermoplastic resin does not become too much compared to the reinforcing fiber, and a laminate with excellent specific strength and specific elastic modulus can be obtained. 2 The mass (g) of the component [C] contained in the prepreg.
[0067] The prepreg of the present invention preferably has a reinforcing fiber content of 30 to 2,000 g / m 2 If the amount of reinforcing fiber is 30g / m 2 If the amount of reinforcing fiber is 2,000 g / m 2 Below, the drapability of the prepreg becomes easy to improve.
[0068] The reinforcing fiber mass content of the prepreg of the present invention is preferably 30 to 90% by mass, more preferably 35 to 85% by mass, and further preferably 40 to 80% by mass. It can be a range formed by a combination of any of the above upper limits and any of the lower limits. If the reinforcing fiber mass content is 30% by mass or more, the amount of resin will not become too much compared to the fiber, and there is an advantage of being easy to obtain a laminate with excellent specific strength and specific elastic modulus. In addition, when the laminate is formed, the heat release during curing is not easy to become excessively high. In addition, if the reinforcing fiber mass content is 90% by mass or less, poor impregnation of the resin is not likely to occur, and the pores of the resulting laminate are prone to become less.
[0069] The laminate of the present invention satisfies the following aspect: the laminate comprises a layer comprising components [A], [C] and [D], [D] being a cured product of an epoxy resin having an average epoxy value of all epoxy resins of 2.0 meq. / g or more and 5.0 meq. / g or less, and the laminate comprises reinforcing fibers [A] contained in both resin regions across a boundary surface between a resin region comprising [C] and a resin region comprising [D].
[0070] The component [D] used in the present invention is a cured product of an epoxy resin having an average epoxy value of all epoxy resins of 2.0 meq. / g or more and 5.0 meq. / g or less. Here, the epoxy value is calculated as described above.
[0071] The presence of [A] included in both resin regions and straddling the boundary surface between the two resin regions can be confirmed by observing a cross section cut perpendicularly to the plane direction of the laminate in the same manner as the confirmation method for the prepreg. Figure 2 To illustrate an example. Figure 2In the observed image 9, in the case of the laminate, the resin region 7 containing the component [C] is in close contact with the resin region 8 containing the component [D], and the surface formed by the resin region 7 containing the component [C] and the resin region 8 containing the component [D] is shown as a boundary surface 10. In addition, a plurality of components [A] 6 are present on the boundary surface 10. The component [A] 6 on the boundary surface 10 is in contact with both the resin region 7 containing the component [C] and the resin region 8 containing the component [D]. In the state where the components [C] and [D] are in contact around the reinforcing fibers, it can be said that the reinforcing fibers are in a state of "being included in these two resin regions across the boundary surface".
[0072] In addition, when looking down at the laminate of the present invention, with respect to the fiber direction of any [A] contained in the above-mentioned two resin regions, at an angle of 45 degrees (whether clockwise or counterclockwise) at a viewpoint perpendicular to the plane direction of the laminate, in a cross section perpendicular to the plane of the laminate including [A] across the above-mentioned two resin regions, that is, in an observed cross section obtained by cutting perpendicularly to the plane direction of the laminate, the cross-sectional curve formed by the boundary surface of the two resin regions is preferably formed by the boundary surface of the two resin regions, and the roughness average length RSm defined by JIS B0601 (2001) is 100 μm or less, and the roughness average height Rc is 3.5 μm or more. More preferably, the roughness average height Rc is 10 μm or more. The lower limit of RSm and the upper limit of Rc are not particularly limited. From the viewpoint that the mechanical bonding force may be reduced due to stress concentration, RSm is preferably 15 μm or more, and Rc is preferably 100 μm or less. The roughness average height Rc and the roughness average length RSm of the cross-sectional curve can be determined by the above-mentioned method in the same manner as the measurement method of the prepreg of the present invention.
[0073] In addition, from the viewpoint of exhibiting excellent mechanical properties, it is preferred that the resin region containing [C] and the resin region containing [D] are each formed in a layered manner and adjacent to each other to form the aforementioned boundary surface. Figure 2 The state in which two continuous resin regions exist adjacent to each other as shown can be confirmed by observing a cross section cut perpendicularly to the plane direction of the laminate.
[0074] By making component [D] of the present invention a cured product of an epoxy resin, a laminate and a molded product excellent in impact bonding strength can be obtained, and therefore it is a preferred embodiment that the cured product of the epoxy resin contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 400 to 3000 based on 100 parts by mass of all epoxy resins contained. In a more preferred embodiment, the cured product of the epoxy resin contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 1000 to 3000 based on 100 parts by mass of all epoxy resins contained.
[0075] As a method for molding the laminate of the present invention, for example, it can be prepared by using molding methods such as press molding, autoclave molding, bag mold molding, tape winding, internal pressure molding, hand lay-up molding, filament winding, pultrusion, resin injection molding, and resin transfer molding.
[0076] The laminate of the present invention can be produced by the following method, that is, by laminating the above-mentioned prepreg of the present invention alone or together with other prepregs to form at least a part of the layer, and then applying pressure and heating to cure it. Here, as a method for applying heat and pressure, for example, a press molding method, an autoclave molding method, a bag molding method, a tape wrapping method, an internal pressure molding method, etc. can be used.
[0077] In the laminate of the present invention, the thermoplastic resin of component [C] is present on the surface or between the layers. Preferably, component [C] is present both on the surface and between the layers. By having component [C] of thermoplastic resin present on the surface of the laminate, the laminate of the present invention can be joined to the same or different parts by welding through component [C]. On the other hand, if component [C] of thermoplastic resin is present between the layers of the laminate, an excellent interlaminar fracture toughness value (G IC and G IIC ).
[0078] For the laminate of the present invention, some heating means can be utilized to make other parts, i.e. parts of the same kind and / or different kinds as the parts constituting the laminate (adherends) be joined with the surface constituent element [C] present in the laminate, so as to be integrated (welded) with the laminate through the constituent element [C]. As different kinds of parts (adherends), parts formed by thermoplastic resins and parts formed by metal materials can be cited. For parts formed by thermoplastic resins, reinforcing fibers, fillers, etc. can also be included. The integration method is not particularly limited, and for example, heat welding, vibration welding, ultrasonic welding, laser welding, resistance welding, induction welding, insert injection molding, injection molding on substrate, etc. can be cited.
[0079] Regarding the strength of the joint of the integrated parts, the tensile shear joint strength measured based on ISO4587:1995 (JIS K6850 (1994)) is preferably 25 MPa or more, more preferably 28 MPa or more. In addition, the out-of-plane tensile joint strength measured based on ASTM D7291-07 is preferably 35 MPa or more, more preferably 40 MPa or more. In addition, the impact joint strength measured based on JIS K6855 (1994) is preferably 6 kJ / m 2 More preferably 9 kJ / m 2 The higher the bonding strength, the better. There is no particular upper limit. In a common integrated laminate, the upper limit of the tensile shear bonding strength is 200 MPa, the upper limit of the out-of-plane tensile bonding strength is 300 MPa, and the upper limit of the impact bonding strength is 50 kJ / m 2 .
[0080] Example
[0081] Hereinafter, the present invention will be described in detail using examples. However, the scope of the present invention is not limited to these examples. It should be noted that the unit "part" of the composition ratio refers to mass parts unless otherwise noted. In addition, for the measurement of various properties, it is carried out under an environment of temperature 23° C. and relative humidity 50% unless otherwise noted.
[0082] <Materials used in Examples and Comparative Examples>
[0083] The following components [A], [B], [C], and [D] were used. The components used in each of the Examples and Comparative Examples are shown in Tables 1 to 3.
[0084] Component [A]: Reinforcement fiber
[0085] ·T800: Carbon fiber ("Torayca (registered trademark)" T800S-24K, manufactured by Toray Co., Ltd., strand tensile strength: 5.9 GPa)
[0086] ·T1100: Carbon fiber ("Torayca (registered trademark)" T1100G-24K, manufactured by Toray Co., Ltd., strand tensile strength: 7.0 GPa)
[0087] T700: carbon fiber ("Torayca (registered trademark)" T700S-24K, manufactured by Toray Co., Ltd., strand tensile strength: 4.9 GPa).
[0088] Component [C]: Thermoplastic resin
[0089] PA6: Made of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Co., Ltd., melting point 225°C)), with a unit weight of 120 g / m 2 membrane
[0090] PP: Polypropylene ("UMEX" (registered trademark) 1010 (manufactured by Sanyo Chemical Co., Ltd., melting point 142°C)) with a unit weight of 120 g / m 2 membrane).
[0091] PEs: polyester ("Hytrel" (registered trademark) 2551 (manufactured by DU PONT-TORAY CO., LTD., melting point 164°C)) with a unit weight of 120 g / m 2 membrane).
[0092] PPS: Made of polyphenylene sulfide ("Torelina" (registered trademark) A670T05 (manufactured by Toray Co., Ltd., melting point 278°C), with a unit weight of 120 g / m 2 membrane
[0093] ·PEEK: Made of polyetheretherketone (PEEK 450G (produced by Victrex, melting point 343°C) with a unit weight of 120 g / m 2 membrane.
[0094] <Preparation method and evaluation method of epoxy resin composition>
[0095] The epoxy resin composition of each specific example described in Table 1 was prepared using the following compounds.
[0096] (1) Epoxy resin
[0097] Bisphenol A type epoxy resin ("jER" (registered trademark) 825, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 175 (g / eq.)
[0098] · Phenol Novolac type epoxy resin ("jER" (registered trademark) 154, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 178 (g / eq.)
[0099] Bisphenol A type epoxy resin ("jER" (registered trademark) 1001, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 475 (g / eq.)
[0100] Bisphenol A type epoxy resin ("jER" (registered trademark) 1004, manufactured by Mitsubishi Chemical Corporation) Epoxy equivalent: 925 (g / eq.)
[0101] Bisphenol A type epoxy resin ("jER" (registered trademark) 1007, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 1975 (g / eq.)).
[0102] (2) Curing agent
[0103] ·4,4'-Diaminodiphenyl sulfone (Seikacure S, manufactured by Wakayama Seika Industries, Ltd.)
[0104] Dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation).
[0105] (3) Curing catalyst
[0106] 3-(3,4-Dichlorophenyl) 1,1-dimethylurea (DCMU99, manufactured by Hodogaya Chemical Industry Co., Ltd.).
[0107] (4) Viscosity regulator
[0108] · Polyvinyl formal ("Vinylec" (registered trademark) K, manufactured by JNC Corporation).
[0109] (5) Preparation method of epoxy resin composition
[0110] In a kneading device, the epoxy resin and viscosity modifier listed in Table 1 were added and heated and kneaded to dissolve the viscosity modifier (however, there was a case where the viscosity modifier was not added). Then, the temperature was lowered to 100° C. or lower while the kneading was continued, and a curing agent and a curing catalyst appropriately selected from those listed in Table 1 were added and stirred to obtain epoxy resin compositions B-1 to B-10.
[0111] <Method for preparing and evaluating epoxy resin cured products>
[0112] The epoxy resin composition prepared by the above method was injected into a mold, and the temperature was raised from 30°C to the curing temperature recorded in Table 1 at a rate of 1.5°C / min in a heat sealing dryer. After heating and curing for the curing time recorded in Table 1, the temperature was lowered to 30°C at a rate of 2.5°C / min to prepare a plate-shaped epoxy resin cured product with a thickness of 2 mm. This is a cured product of the epoxy resin of component [B] and a cured product of the epoxy resin of component [D]. Based on the obtained epoxy resin cured product, each specific example recorded in Table 1 was evaluated by the following method.
[0113] <Measurement method of flexural fracture strain and flexural strength of epoxy resin cured products>
[0114] A rectangular test piece with a length of 60 mm and a width of 10 mm was cut out from the plate-shaped resin cured product prepared by the above method, and the test piece was dried in a vacuum oven at 60°C for 24 hours. A three-point bending test was performed using a universal testing machine (manufactured by Instron Japan Company Limited, "Instron" (registered trademark) 5565 Model P8564) at a test speed of 2.5 mm / min and a distance between support points of 32 mm. The bending fracture strain and bending strength were determined in accordance with JIS K7171 (1994).
[0115] <Method for measuring melting point of thermoplastic resin>
[0116] The melting point of the thermoplastic resin is measured using a differential scanning calorimeter (DSC) in accordance with JIS K7121 (2012). When a plurality of melting points are observed for a mixture or the like, the highest melting point is adopted as the melting point of the thermoplastic resin.
[0117] <Method for preparing prepreg>
[0118] Prepregs were prepared by the following two methods. The components used in each example are shown in Tables 2 and 3, respectively.
[0119] Prepreg [I]
[0120] The component [A] reinforcing fiber (weight per unit area 193g / m 2 ) is pulled out into a reinforcing fiber sheet arranged in a continuous state in one direction, and the reinforcing fiber sheet is made to advance in one direction, and the unit area weight of the component [C] is 120 g / m 2The resin sheet of the continuous reinforcing fiber sheet was arranged, and the component [C] was melted by heating with an IR heater and attached to the entire surface of one side of the continuous reinforcing fiber sheet. The material impregnated in the reinforcing fiber sheet was cooled to obtain a fiber-reinforced resin intermediate. The epoxy resin composition related to the selected component [B] as shown in Tables 2 and 3 was coated with a knife coater at a resin unit weight of 100 g / m 2 The epoxy resin film is coated on release paper, and then the epoxy resin film is overlapped on the surface of the intermediate opposite to the surface impregnated with the component [C], and the epoxy resin composition is impregnated into the intermediate while heating and pressing with a hot roller to obtain a prepreg [I].
[0121] Prepreg[II]
[0122] The epoxy resin composition related to the selected component [B] as shown in Tables 2 and 3 was coated with a knife coater at a resin unit area weight of 50 g / m 2 The resin film was coated on release paper. The resin film was overlapped on the reinforcing fibers (weight per unit area 193 g / m2) of the component [A] aligned in one direction. 2 ) on both sides, and the epoxy resin composition is impregnated into the carbon fibers while heating and pressing using hot rollers to obtain a prepreg [II].
[0123] <Preparation method of laminate and evaluation of mechanical properties>
[0124] (1) Determination method of tensile shear bond strength
[0125] The prepregs [I] and [II] prepared above were cut into predetermined sizes to obtain two prepregs [I] and six prepregs [II]. The axial direction of the reinforcing fibers was defined as 0°, and the axial orthogonal direction was defined as 90°, and the [0° / 90°] 2s (symbol s represents mirror symmetry) are stacked to prepare a preform. At this time, the two outermost layers of each side of the preform are stacked in a manner that becomes a prepreg [I]. That is, two prepregs [I] are stacked with six prepregs [II]. The two surface layers of the preform are configured in a manner that becomes a thermoplastic resin layer containing the constituent element [C]. That is, the surface of the prepreg [I] impregnated with the constituent element [C] is configured to be the outside. The preform is set in a press molding die, and a clamp and a spacer are used as needed. While maintaining the shape, a pressure of 0.6MPa is applied with a press, and heated under the conditions described in Tables 2 and 3, thereby obtaining a laminate. The presence position of the constituent element [C] is the surface of the laminate.
[0126] The obtained laminate was cut into two pieces with a width of 250 mm and a length of 92.5 mm, with the 0° direction being the length direction of the test piece, and dried in a vacuum oven for 24 hours. After that, the two pieces cut into a shape with a width of 250 mm and a length of 92.5 mm were overlapped with a width of 25 mm × a length of 12.5 mm with the 0° direction being the length direction, and a pressure of 3 MPa was applied at a temperature 20°C higher than the melting point of the thermoplastic resin used as the component [C], and maintained for 1 minute, thereby welding the overlapped surfaces to obtain an integrated molded product. According to ISO4587:1995 (JIS K6850 (1994)), a tab was bonded to the obtained integrated molded product, and cut into a width of 25 mm to obtain the target test piece.
[0127] The obtained test piece was dried in a vacuum oven for 24 hours, and the tensile shear bonding strength was measured at an ambient temperature of 23° C. in accordance with ISO 4587:1995 (JIS K6850 (1994)), and the evaluation was performed as follows based on the measurement results. The results are shown in the table.
[0128] 28MPa or above: A
[0129] 25MPa or more and less than 28MPa: B
[0130] 20MPa or more and less than 25MPa: C
[0131] Less than 20MPa: D (unqualified).
[0132] (2) Method for measuring impact bond strength
[0133] The prepregs [I] and [II] prepared above are cut into a specified size, and a total of 52 prepregs are stacked in a manner that the two outermost layers of each of the two sides of the preform are set as prepregs [I], 50 prepregs [II] are sandwiched between them, and all have the same reinforcing fiber direction, and a preform is prepared. At this time, the two surface layers of the preform are configured in a manner that the thermoplastic resin layer containing the component [C] is configured. That is, it is configured so that the surface of the prepreg [I] impregnated with the component [C] becomes the outside. Similarly, the two outermost layers of each of the two sides of the preform are set as prepregs [I], 103 prepregs [II] are sandwiched between them, and the same reinforcing fiber direction is formed, and a total of 105 sheets are stacked, and the two surface layers are configured in a manner that the thermoplastic resin layer containing the component [C] is configured to prepare the preform. That is, it is configured so that the surface of the prepreg [I] impregnated with the component [C] is on the outside. The two preforms were placed in a press mold, using jigs and spacers as needed, and a pressure of 0.6 MPa was applied by a press machine while maintaining the shape, and heated under the molding conditions described in Table 2 or 3, thereby obtaining two laminates with a thickness of about 10 mm and a thickness of about 20 mm. The component [C] was present on the surface of the laminate.
[0134] The axial direction of the reinforcing fiber is used as the length direction of the test piece, and the obtained laminate with a thickness of about 10 mm is cut into a quadrilateral with a width of 250 mm and a length of 25 mm. In addition, the axial direction of the reinforcing fiber is used as the length direction of the test piece, and the obtained laminate with a thickness of about 20 mm is cut into a quadrilateral with a width of 250 mm and a length of 45 mm, and the obtained two panels are dried in a vacuum oven for 24 hours. Afterwards, the two panels are overlapped to form the same reinforcing fiber axial direction, and a pressure of 3 MPa is applied at a temperature 20 ° C higher than the melting point of the thermoplastic resin used as the constituent element [C], and maintained for 1 minute, thereby welding the joint surface to obtain an integrated molded product. The obtained integrated molded product is cut with a width of 25 mm to obtain the target test piece.
[0135] The obtained test piece was dried in a vacuum oven for 24 hours, and the impact bonding strength was measured based on JIS K6855 (1994) with the surface perpendicular to the reinforcing fiber axial direction as the surface receiving impact, and the evaluation was performed as follows based on the measurement results. The results are shown in the table.
[0136] 9kJ / m 2 Above: A
[0137] 6kJ / m 2 Above and less than 9kJ / m 2 :B
[0138] 3kJ / m2 Above and less than 6kJ / m 2 :C
[0139] Less than 3kJ / m 2 :D (failed).
[0140] (3) Method for measuring out-of-plane tensile bond strength
[0141] The prepregs [I] and [II] prepared above are cut into a specified size, and a total of 75 prepregs are stacked in a manner that the two outermost layers of each of the two sides of the preform are prepregs [I], 73 prepregs [II] are sandwiched therebetween, and all of them have the same reinforcing fiber direction, to prepare a preform. At this time, the two outermost layers of each side are stacked in a manner that they become prepregs [I], and the two surface layers of the preform are configured to become thermoplastic resin layers containing constituent element [C]. The preform is set in a press molding die, and a clamp and a spacer are used as needed. A pressure of 0.6MPa is applied by a press machine while maintaining the shape, and the molding conditions described in Table 2 or 3 are heated to obtain a laminate. The presence position of constituent element [C] is the surface of the laminate.
[0142] The reinforced fiber composite material plate obtained was cut into two quadrilateral plates with a width of 250 mm and a length of 125 mm, with the reinforcing fiber axis as the length direction of the test piece, and dried in a vacuum oven for 24 hours. After that, the two plates were overlapped in the same reinforcing fiber axial direction, and a pressure of 3 MPa was applied at a temperature 20°C higher than the melting point of the thermoplastic resin used as the component [C], and maintained for 1 minute, thereby welding the joint surface to obtain an integrated molded product. The obtained integrated molded product was ground into a spool shape with an outer diameter of 25 mm, an inner diameter of 19 mm, and a measured length of 6.4 mm to obtain the target test piece.
[0143] The obtained test piece was dried in a vacuum oven for 24 hours, and the out-of-plane tensile bonding strength was measured in accordance with ASTM D7291-07, and the following evaluation was performed based on the measurement results. The results are shown in the table.
[0144] 40MPa or above: A
[0145] 35MPa or more and less than 40MPa: B
[0146] 30MPa or more and less than 35MPa: C
[0147] Less than 30MPa: D (unqualified).
[0148] (4) Interlaminar fracture toughness value (G IC and G IIC)
[0149] The prepreg [I] prepared as above is cut into a predetermined size, and all 20 prepregs are stacked with the surface having the component [C] facing upward so as to have the same direction of the reinforcing fibers. At this time, a release film for introducing precracks is sandwiched between the 10th and 11th sheets in the center to prepare a preform. The preform is set in a press molding die, and a clamp and a spacer are used as needed. While maintaining the shape, a pressure of 0.6 MPa is applied by a press machine, and a laminate is obtained under the molding conditions described in Table 2 or 3. The component [C] is present between the layers of the laminate and on the surface of one side.
[0150] A rectangular test piece with a length of 150 mm and a width of 20 mm was cut from the obtained laminate with the reinforcing fiber axis as the longitudinal direction of the test piece, and dried in a vacuum oven at 60°C for 24 hours. The obtained test piece was evaluated for interlaminar fracture toughness value (G IC and G IIC ).
[0151] <Measurement of the mean roughness length RSm and the mean roughness height Rc of the prepreg or laminate>
[0152] The prepreg [I] or laminate prepared as described above is used. Figure 1 As shown, in the case of a prepreg, with respect to any fiber direction 4 of [A] contained in the above two resin regions, an observation cross section 5 cut perpendicularly to the plane direction of the prepreg at a 45-degree angle when viewed from a viewpoint perpendicular to the plane direction of the prepreg is photographed using an optical microscope at 1000 times. Within an arbitrary 500 μm square observation range in the obtained image, the roughness average length RSm and the roughness average height Rc defined by JIS B0601 (2001) of the cross-sectional curve element obtained by the above-mentioned cross-sectional curve element measurement method 1 are measured. The same is true for the case of a laminate.
[0153] <Examples 1 to 14>
[0154] In Examples 1 to 14, laminates were prepared by the method described in (1) the method for measuring tensile shear bond strength, (2) the method for measuring impact bond strength, and (3) the method for measuring out-of-plane tensile bond strength.
[0155] <Example 1 and Comparative Examples 1 and 2>
[0156] In Example 1, as shown in Table 2, by using an epoxy resin having an average epoxy value of 3.9 meq. / g as component [B], compared with Comparative Examples 1 and 2 shown in Table 3, the integrated molded product showed excellent impact bonding strength and out-of-plane tensile bonding strength.
[0157] <Examples 1 to 6>
[0158] As shown in Table 1, epoxy resins having different average epoxy values were used in Examples 1 to 6. As shown in Table 2, when the average epoxy value was high, the impact bonding strength tended to be slightly reduced, and when the average epoxy value was low, the out-of-plane tensile bonding strength tended to be slightly reduced, but within the range of the average epoxy value in Examples 1 to 6, various excellent bonding strengths were shown.
[0159] <Example 1 and Example 7>
[0160] As shown in Table 1, in Example 7, a curing agent different from that in Example 1 was used, and as shown in Table 2, various excellent bonding strengths similar to those in Example 1 were exhibited.
[0161] <Example 1 and Example 8>
[0162] As shown in Table 1, Example 8 was prepared in the same manner as Example 1 except that no viscosity modifier was used. As shown in Table 2, Example 8 showed various excellent bonding strengths similar to those of Example 1.
[0163] <Example 1 and Examples 9 and 10>
[0164] As shown in Table 2, in Examples 9 and 10, reinforcing fibers having different strand tensile strengths were used. As compared with Example 1, the higher the strand tensile strength, the higher the tensile shear bond strength and the out-of-plane tensile bond strength, showing preferred characteristics.
[0165] <Example 1 and Examples 11 to 14>
[0166] As shown in Table 2, in Examples 11 to 14, although different components [C] from those in Example 1 were used, various excellent bonding strengths similar to those in Example 1 were exhibited.
[0167] <Example 1 and Comparative Example 3>
[0168] In Comparative Example 3, a film having a unit area weight of 50 g / m2 was attached to both sides of a reinforcing fiber sheet arranged in a plane in one direction. 2A film of polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Co., Ltd.)) was heated and pressed at 250°C to obtain a reinforced carbon fiber with a unit weight of 193 g / m 2 The obtained prepreg was cut into a predetermined size and used for tensile shear bonding strength evaluation at [0° / 90°] 2s The prepregs were stacked in a structure. For the purpose of evaluating the impact bonding strength, two types of prepregs were used, 52 of which were stacked in the same direction of reinforcing fibers and 105 of which were stacked. For the purpose of evaluating the out-of-plane tensile bonding strength, 75 prepregs were stacked in the same direction of reinforcing fibers. A pressure of 3 MPa was applied to the obtained stacked prepregs using a press and heated at 250°C for 10 minutes to obtain each laminated board. The tensile shear bonding strength, impact bonding strength and out-of-plane tensile bonding strength were measured from the obtained laminated body by the method described in the examples. As shown in Table 3, since the laminated body plate of Comparative Example 3 does not contain epoxy resin, the out-of-plane tensile strength is low compared with that of Example 1, and it does not show sufficient properties as a structural material.
[0169] <Example 15 and Comparative Examples 4 and 5>
[0170] In Example 15, (4) interlaminar fracture toughness value (G IC and G IIC ) is prepared by the method described in the determination method of . The above-mentioned prepreg [I] is cut into a specified size, and all the prepregs totaling 20 sheets are stacked with the surface containing the component [C] facing upward in a manner that the reinforcing fibers have the same direction. A release film for introducing precracks is sandwiched between the 10th and 11th sheets in the center to prepare a preform. In Comparative Example 4, the prepreg [II] (not containing the component [C]) is cut into a specified size, and stacked in the same manner as in Example 15, and a release film is sandwiched to obtain a preform. In Comparative Example 5, polyamide particles (SP-500, manufactured by Toray Co., Ltd.) are added so that the particle amount per unit area of the prepreg becomes 7g / m 2 After being evenly spread in a manner, the preform was laminated on one side of a prepreg [II] (not including component [C]) cut into a predetermined size in the same manner as in Example 15, and a release film was sandwiched therebetween to obtain a preform. In both Example 15 and Comparative Examples 4 and 5, a pressure of 0.6 MPa was applied to the obtained preform by a press machine, and the preform was heated at 135°C for 120 minutes to obtain a laminate, and then the interlaminar fracture toughness value (G IC and G IICAs shown in Tables 2 and 3, Example 15 including the component [C] between the layers of the laminate exhibited an excellent interlaminar fracture toughness value compared to Comparative Example 4 not including the component [C] and Comparative Example 5 including the thermoplastic resin in a different form.
[0171] [Table 1]
[0172]
[0173] [Table 2-1]
[0174]
[0175] [Table 2-2]
[0176]
[0177] [Table 3]
[0178]
[0179] Description of Reference Numerals
[0180] 1: One layer of a prepreg or laminate
[0181] 2: Constituent elements [A]
[0182] 3: Component [C] and component [B] or component [C] and component [D]
[0183] 4: Axial direction of any fiber bundle
[0184] 5: Observe the cross section
[0185] 6: Constituent elements [A]
[0186] 7: Resin area including component [C]
[0187] 8: A resin region including component [B] or a resin region including component [D]
[0188] 9: Observe the image
[0189] 10: Boundary surface
[0190] 11: Baseline
[0191] 12: Baseline vertical line
[0192] 13: Section curve
Claims
1. A prepreg comprising the following components [A], [B] and [C]: [A] Reinforcement fibers; [B] Epoxy resin; [C] Thermoplastic resin, The average epoxy value of all epoxy resins contained in [B] is 3.1 meq. / g or more and 5.0 meq. / g or less, [C] exists on the surface of the prepreg, In the prepreg, there are reinforcing fibers [A] included in the resin region [B] and the resin region [C] across the boundary between the two resin regions, The resin region containing [B] and the resin region containing [C] are each formed in a layer shape and are adjacent to each other, thereby forming the boundary surface.
2. The prepreg according to claim 1, wherein In the prepreg when viewed from above, when a cross section perpendicular to the plane of the prepreg containing the [A] is obtained from a direction that differs by 45 degrees from the fiber direction of any [A] contained in the two resin regions, in the cross section, the cross-sectional curve formed by the closely fitting boundary surfaces of the two resin regions has a roughness average length RSm defined by JIS B0601 (2001) of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
3. The prepreg according to claim 1 or 2, wherein: The average epoxy value of all epoxy resins contained in component [B] is 3.1 meq. / g or more and 4.0 meq. / g or less.
4. The prepreg according to any one of claims 1 to 3, wherein Component [B] contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 400 to 3000 or less, based on 100 parts by mass of the total epoxy resin contained.
5. The prepreg according to claim 4, wherein Component [B] contains 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 1000 or more and 3000 or less, based on 100 parts by mass of the total epoxy resin contained.
6. The prepreg according to any one of claims 1 to 5, wherein In component [B], the bending fracture strain in a state where the degree of cure is 90% or more is 8% or more.
7. The prepreg according to any one of claims 1 to 6, wherein Component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more.
8. The prepreg according to any one of claims 1 to 7, wherein The roughness average height Rc is greater than or equal to 10 μm.
9. A laminate comprising a layer comprising the following components [A], [C] and [D]: [A] Reinforcement fibers; [C] Thermoplastic resin; [D] Epoxy resin cured product, [D] is a cured product of an epoxy resin having an average epoxy value of all epoxy resins of 3.1 meq. / g or more and 5.0 meq. / g or less, In the laminate, there are reinforcing fibers [A] included in the resin region [C] and the resin region [D], straddling the boundary between the two resin regions. The resin region containing [C] and the resin region containing [D] are each formed in a layer shape and are adjacent to each other, thereby forming the boundary surface.
10. The laminate according to claim 9, wherein In the stacked body viewed from above, when a cross section perpendicular to the plane of the stacked body containing the [A] is obtained from a direction that differs by 45 degrees from the fiber direction of any [A] contained in the two resin regions, in the cross section, the cross-sectional curve formed by the closely fitting boundary surfaces of the two resin regions has a roughness average length RSm defined by JIS B0601 (2001) of less than 100 μm and a roughness average height Rc of more than 3.5 μm.
11. The laminate according to claim 9 or 10, wherein There are constituent elements [C] on the surface.
12. The laminate according to any one of claims 9 to 11, wherein There are constituent elements [C] between the layers.
13. The laminate according to any one of claims 9 to 12, wherein Component [D] is a cured epoxy resin containing 20 parts by mass or more and 50 parts by mass or less of a bisphenol-type epoxy resin having an epoxy equivalent of 1000 or more and 3000 or less, based on 100 parts by mass of all epoxy resins contained.
14. The laminate according to any one of claims 9 to 13, wherein The roughness average height Rc is greater than or equal to 10 μm.
15. The laminate according to any one of claims 9 to 14, wherein Component [A] contains carbon fibers having a strand tensile strength of 5.5 GPa or more. 16 . The laminate according to claim 11 , wherein at least a part of the layers is formed by a cured product of the prepreg according to claim 1 .
17. A molded article in which the laminate according to any one of claims 11 to 16 is integrated with other members by bonding to the surface of component [C].
Citation Information
Patent Citations
Prepreg and fiber-reinforced composite material
JP1996259713A
Carbon fiber reinforced resin molded product and its manufacture
JP1998138354A
Adhesion structural member
JP2018161801A
Prepreg, prepreg laminate, and fiber-reinforced composite material
WO2018066600A1